Gas cylinders. Design, construction and testing of refillable composite gas cylinders and tubes. Fully wrapped fibre reinforced composite gas cylinders and tubes up to 450 l with non-load-sharing metallic or non-metallic liners or without liners Part 3, (26th July 2023) - British Standards Institution,
No abstract available